Spirala i narodziny. O wczesnej poezji Izabeli Morskiej - Sobolczyk, Piotr (Zagadnienia Rodzajów Literackich, 2024)
The article analyses Izabela Morska’s collection of poems 1983. Maszynopisy published in 2023. At first the author analyses the idea of “regained” poems (all written between 1980– 1985 and never published until now) and the “regained decade” in the history of Polish feminine poetry. Morska was a female dissident, a phenomenon quite suppressed in the history of the Solidarity movement. She also participated in an unofficial literary life with other girls who were also poets, andb sometimes her lovers. The beginning of the article analyses this topic according to Morska’s introductory essay. The author offers in the article the idea of “spiral regaining” Morska’s youth (alluding to the title of her first published book, Death and Spiral). As for female writers who were Morska’s peers, the author mentions Anna Janko and most of all Eda Ostrowska. Subsequently three main topics are studied. 1) The idea of a “national hero” and dissident who could never be a woman. Morska was aware of her exclusion as a woman from the dominant dissident movement and also from literary life, and these two overlapped. Especially the long poem King of Rats IV is a point in case. 2) The negative motherhood appears in the poems, but also in the cycle of “poems in prose” and is compared to Morska’s gothic novel Alma (written in 1986 and published in 2003). The author suggests in the article that some of these poems in prose constitute “Pre-Alma”. 3) Rape as a metaphor or, rather, symbolization, and its place in the attempt to create a personal and strongly feminine mythology. For Morska, rape might signify sexual harassment (and as such is a recurring theme in Death and Spiral, Absolute Amnesia, Alma…), but also metaphorically any kind of movement, including birth and death leading to rebirth, marked with violence. Symbolization is defined in the article according to Jean Laplanche and Marguerite Sechehaye.